Therapies in non‐alcoholic steatohepatitis (NASH). (January 2017) - Oseini, Abdul M.; Sanyal, Arun J.
Abstract: The hallmark of non‐alcoholic fatty liver disease (NAFLD) is excessive fatty accumulation in the hepatocytes, which may be an isolated event (non‐alcoholic fatty liver, NAFL) or accompanied by evidence of inflammation and cell injury with or without fibrosis (non‐alcoholic steatohepatitis, NASH). NASH, the more aggressive form of NAFLD, may progress to cirrhosis and hepatocellular carcinoma. Since NASH is estimated to overtake hepatitis C virus infection as the leading cause of liver transplantation in the US in the coming decade, and there are no current FDA‐approved therapies for this disease, the need to find appropriate therapeutic targets is now more urgent than ever before. Diet and other lifestyle modifications have always been difficult to maintain and this approach alone has not slowed the rising tide of the disease. While the results of traditional therapies such as vitamin E and pioglitazone have been significant for steatosis and inflammation, they have had no effect on fibrosis, which is the strongest indicator of mortality in this condition. However, the understanding of the pathogenesis and progression of NASH has evolved and several promising novel therapies to target and possibly reverse fibrosis are being evaluated, making the future outlook of NASH therapy more optimistic.